2021
DOI: 10.1002/ajim.23222
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 as an occupational disease

Abstract: The impact of coronavirus disease 2019 (COVID‐19) caused by the severe acute respiratory syndrome coronavirus 2 permeates all aspects of society worldwide. Initial medical reports and media coverage have increased awareness of the risk imposed on healthcare workers in particular, during this pandemic. However, the health implications of COVID‐19 for the global workforce are multifaceted and complex, warranting careful reflection and consideration to mitigate the adverse effects on workers worldwide. Accordingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
162
0
12

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(177 citation statements)
references
References 86 publications
(94 reference statements)
3
162
0
12
Order By: Relevance
“…Zgodnie ze stanowiskiem Ministra Zdrowia brak jest w związku z tym podstawy do zmiany przepisów, ponieważ w świetle obecnie obowiązujących norm COVID-19 jest chorobą zakaźną, co oznacza, że stwierdzenie wystąpienia choroby zawodowej będzie odbywało się na zasadach ogólnych -takich jak w przypadku innych chorób zakaźnych. W literaturze anglojęzycznej również uznaje się COVID-19 za chorobę zawodową [36].…”
Section: Covid-19 Jako Choroba Zawodowaunclassified
“…Zgodnie ze stanowiskiem Ministra Zdrowia brak jest w związku z tym podstawy do zmiany przepisów, ponieważ w świetle obecnie obowiązujących norm COVID-19 jest chorobą zakaźną, co oznacza, że stwierdzenie wystąpienia choroby zawodowej będzie odbywało się na zasadach ogólnych -takich jak w przypadku innych chorób zakaźnych. W literaturze anglojęzycznej również uznaje się COVID-19 za chorobę zawodową [36].…”
Section: Covid-19 Jako Choroba Zawodowaunclassified
“…The study will also estimate how occupational risks of exposure to COVID-19 vary across sociodemographic characteristics. Indeed, the pandemic has revealed that the occupational factor of risk of exposure to COVID-19 is strongly associated with educational and socioeconomic status, which can contribute to higher rates of infection [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clusters of human SARS-CoV-2 infections (COVID- 19) have been observed worldwide in a variety of private, public and occupational settings. Not only workers in healthcare but also workers in other essential services/industries like the food producing industry face an increased risk 1 . Exceptionally many SARS-CoV-2 outbreaks were reported in meat processing plants across Europe, Australia and the Americas [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…high density of workers, enhanced breathing and yelling due to the physically intense work and noisy environment), societal and/or economic factors (e.g. migrant workers sharing housing and transportation), and the climate conditions inside the production rooms [1][2][3]6 . The low temperature, which is in place to ensure food safety, combined with presence of air recirculation systems to reduce energy use, are suggested to be advantageous for persistence and circulation of SARS-CoV-2 in air.…”
Section: Introductionmentioning
confidence: 99%